The Puente Piedra Group in the Lima area and the demise of Jurassic arc volcanism along the Gondwana margin of Peru: The conundrum of The Oyotun Formation and its bewilldering correlation with the Misahualli Formation - Aleman R., Antenor M. (2021)
The lower part of the Puente Piedra Group consists of thick bedded porphyritic to aphanitic basalts and basaltic andesite lava flows interbedded with medium bedded lithic to crystal lapilli tuffs known as the Tambo Inga Formation. The middle unit consists of varycolor tuffaceous shales interbedded with ash tuffs and thinly bedded fine grained lapilli tuffs that contain a rich Berriasian to Tithonian age fauna known as the Puente Inga Formation. The uppermost unit consists thick bedded massive porphyritic to aphanitic interbedded with coarse grained lapilli tuffs with rests of plants and well stratified pyroclastic breccias that toward the top contain abundant calcareous lapilli tuffs and recurrent varycolor tuffaceous shales that resemble the Middle unit and it is known as the Ventanilla Formation. Northward, between Piedras Gordas and Playa Ancon this unit is more than 1523 meters and it is dominated by porphyritic massive lava flows with abundant hyaloclastic breccias. The Puente Piedra Group and the correlative Oyotun and Guaneros formation documents the last stages of the Jurassic arc. Indeed, the Mesozoic arc initiated in Central Chile Margin during the Early Triassic continued throughout the Cretaceous along the Chilean margin. However; near the Peru-Chile border, this volcanic arc suddenly fades away during the Neocomian approach and subduction of an oceanic plateau. As a result, the subduction shallowed and was accompanied by extensional uplift of the Maranon and Paracas terranes and concomitant quartz-rich provenance change nourished by these terranes. Although, the Puente Piedra Group and the Guaneros and Oyotun formations have very similar normalized chondrite patterns that fluctuate from E-MORB and OIB caused by hyper-extension that boudinage the crust and brought up deeper fertile mantle during adiabatic decompression melting. However, while the Puente Piedra and Upper Guaneros have a gentle LREE slope and almost concave HREE with subtle negative Eu anomaly, the samples from the Oyoutun Formation have a spiky pattern with a distinctive signature branded by Tb-enrichment that it is difficult to explain (Fig. 1). Because of the pervasive intraplate extension coeval with enriched mantle upwelling, the Misahualli has similar chondrite pattern which perhaps was correlated with this unusual arc sequences. Indeed, while the Misahualli Formation was associated to a regional intraplate volcanism and extension prior to the opening of the South Atlantic, the Late Jurassic units along the coast of Peru were linked to a volcanic arc that underwent hyper-extension during oblique convergence. Finally, it is difficult to conceive a geotectonic correlation between the Misahualli Formation and the Jurassic Oyotun-Colan-Traposa formations. While the first unit has only been mapped east of the accreted Paleozoic terranes in Ecuador and it was developed during intraplate extension; the coastal units occurred only east of the Maranon Block and was part of a continental arc characterized by important E-MORB and OIB signatures. The broad variation in high in this diagram is related to removal of olivine, plagioclases and pyroxenes during fractionation and the relatively flat HREE perhaps reflects the absence of deep garnet. The normalized N-MORB diagram depicts a strong correlation between the Upper Guaneros and Oyotun formations with the Puente Piedra. The diagram shows a strong enrichment in LIL that is less pronounced in the Oyotun samples, however there is a slight depletion in the more HFS with higher enrichment in Pb and Sr and strong depletion in Nb typical of subduction related volcanic arcs.